Digital Health Literacy amongst Hypertensive Clients in Depok City - Fathurrahman, Sofyan Dwi; Rachmawati, Utami; Sukihananto, Sukihananto; Wiarsih, Wiwin (Poltekkes Kemenkes Banjarmasin, 2024)
The still-growing of e-health integration in Depok City's hypertension prevention and control initiatives is at odds with the city's development goal for 2021–2026, which calls for the creation of contemporary public services and the development of technology–based infrastructure. This study aims to identify the digital health literacy in hypertensive clients in Depok City. With the greatest estimated population of hypertensive clients in Depok City, the research approach is a descriptive study using the I-eHEALS questionnaire with cluster sampling technique on hypertensive clients in five urban villages, with up to 100 samples. The findings revealed that most Depok City's hypertensive clients were young adults (64%), female (72%), with a secondary education level of 59% (junior high school, high school, or equivalent), and 25% of them used YouTube as a source of digital health information. Furthermore, it is also reported that hypertensive clients in Depok City have a digital health literacy level of 26. The study's findings indicate that hypertensive clients in Depok City tend to be more digitally literate when they are young adults, female, have higher levels of education, and use online health applications as a source of information about digital health. However, these clients still struggle to assess, evaluate, and feel confident when using digital health information. The researcher suggests fostering digital health literacy and creating digital health resources with an emphasis on hypertension patients' self-care management.